Antimicrobial Activity of Endophyte Bacteria Isolated from Seaweed (Padina sp.) on the Growth of Bacteria Escherichia coli and Staphylococcus aureus - Akay, Fanesa; Ngangi, Jantje; Lawalata, Helen J (Universitas Labuhanbatu, 2023)
Padina sp. seaweed is one of the Chlorophyta which has potential as an antimicrobial. This study aimed to determine the antimicrobial activity of Padina sp. seaweed endophytic bacteria against Escherichia coli and Staphylococcus aureus. The method used in this research is descriptive qualitative. The results of the isolation of endophytic microbes of Padina sp. seaweed obtained were seven isolates DP1, DP2, DP3, DP4, AP1, AP2, and AP3. The results of the antimicrobial activity test showed that the seven isolates of endophytic bacteria had potential as antimicrobials. Incubation time for 24 hours showed that the diameter of the inhibition zone formed was 9.75 – 11.55 mm against S. aureus and 7.15 – 10.0 mm against bacteria. E. coli. The AP3 and DP1 isolates had a wider zone, presumably because their antibacterial substances were higher than the other isolates.